Utilization of Multifunctional Environment‐Friendly Organic Dopants Inspired from Nature for Carbon Nanotube‐Based Planar Heterojunction Silicon Solar Cells - Jiye Han; Jeong-Seok Nam; Seungju Seo; Aram Lee; Changhyun Lee; Sangeun Park; Yoonmook Kang; Hae-Seok Lee; Donghwan Kim; Qiang Zhang; Hyokyung Sung; Esko I. Kauppinen; et al. (Advanced Energy & Sustainability Research, 2022)
Herein, eco‐friendly natural acids inspired by nature, namely, acetic acid, formic acid, lactic acid, and citric acid on their capability of functioning as a p‐dopant for the carbon nanotube transparent electrode in silicon‐based planar heterojunction solar cells, are tested. From the result, lactic acid shows the multifunctional effect of p‐doping with excellent doping stability as well as antireflection. The doping effect and its stability are investigated by diverse methods, such as van der Pauw four‐probe measurement as well as Raman, photoelectron yield, and absorption spectroscopy. The sheet resistance decreases by 22.1% when carbon nanotube films are doped by lactic acid and the doped films are stable for more than 20 days. The antireflection effect of lactic acid coating is confirmed by atomic force microscopy, ellipsometry, computational analyses, and reflectance spectroscopy. The power conversion efficiency of carbon nanotube‐laminated silicon solar cells improves from 8.2% to 10.3% by using nature‐inspired lactic acid. Such a great improvement is ascribed to not only the p‐doping and antireflection effects but also the passivation effect of lactic acid on the Si surface defect sites as evidenced by both the Fourier‐transform infrared and the Quasi‐steady‐state photoconductance lifetime measurements.